2010
DOI: 10.1155/2010/820580
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of fingernails: A novel tool for evaluation of bone quality?

Abstract: Abstract. Raman data from human fingernails has been analysed to determine if a relationship exists between spectral features and bone quality. Previous work demonstrated a relationship between the manually determined intensity of the disulphide peak (Bone Quality Test; BQT) and osteoporotic fracture. A computer program is now described that automates the BQT determination for large sample-sets. In this study the ability of the automated BQT to discriminate between fractures and controls was compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
(33 reference statements)
2
14
0
3
Order By: Relevance
“…A number of key features are apparent in this figure, and assignments of common bands in proteins are provided in Table . In keeping with previous findings, there is a change in the region where the disulphide mode is found, just above 500 cm −1 , with the mean nonfracture spectrum exhibiting a more intense feature centred around 507 cm −1 , while the mean fracture spectrum shows a broader flatter peak centred around 521 cm −1 . Table summarizes the different amino acid residue assignments that could be made against the full spectra.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…A number of key features are apparent in this figure, and assignments of common bands in proteins are provided in Table . In keeping with previous findings, there is a change in the region where the disulphide mode is found, just above 500 cm −1 , with the mean nonfracture spectrum exhibiting a more intense feature centred around 507 cm −1 , while the mean fracture spectrum shows a broader flatter peak centred around 521 cm −1 . Table summarizes the different amino acid residue assignments that could be made against the full spectra.…”
Section: Resultssupporting
confidence: 82%
“…In this study, only samples meeting the DXA score criteria at all three sites (femoral neck, wrist and vertebrae) measured were included in the respective group, to create a set of samples from participants with pervasive osteoporosis (standard osteoporosis definition as recommended by the WHO is that only one out of three sites needs to meet this threshold). Previous studies have suggested that the Raman changes to nails due to osteoporosis are subtle, so a more extreme set of criteria was applied to enhance the contrast between the two groups. Throughout the paper, ‘healthy’ is used to describe samples that were classified as ‘normal’ through DXA assessment, unless clarified otherwise or if used in a context unrelated to discussing samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only rare reports have been devoted to the keratin structure in nails. It has been investigated in the context of some diseases [18][19][20][21][22][23][24][25] and aer chemical or physical modication. [26][27][28][29] In our opinion, the diagnosis of systemic diseases, based on the ngernail protein composition and structure, rstly requires a comprehensive examination of the keratin structure in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A number of characteristics define the mechanical properties of bone. The main characteristics, which vary across multiple scales , are often referred to as bone quality , such as geometry and architecture ; material composition, organization and cross‐links ; microdamage ; and bone turnover and remodeling . All these characteristics are highly influenced by individual external (e.g., adaptation to loading conditions) and internal (e.g., aging and disease) factors.…”
Section: Introductionmentioning
confidence: 99%